Fluorinating the Solid Electrolyte Interphase by Rational Molecular Design for Practical Lithium‐Metal Batteries - Xie, Jin; Sun, Shu‐Yu; Chen, Xiang; Hou, Li‐Peng; Li, Bo‐Quan; Peng, Hong‐Jie; Huang, Jia‐Qi; Zhang, Xue‐Qiang; Zhang, Qiang (Angewandte Chemie International Edition, 2022)
The lifespan of practical lithium (Li)‐metal batteries is severely hindered by the instability of Li‐metal anodes. Fluorinated solid electrolyte interphase (SEI) emerges as a promising strategy to improve the stability of Li‐metal anodes. The rational design of fluorinated molecules is pivotal to construct fluorinated SEI. Herein, design principles of fluorinated molecules are proposed. Fluoroalkyl (−CF2CF2−) is selected as an enriched F reservoir and the defluorination of the C−F bond is driven by leaving groups on β‐sites. An activated fluoroalkyl molecule (AFA), 2,2,3,3‐tetrafluorobutane‐1,4‐diol dinitrate is unprecedentedly proposed to render fast and complete defluorination and generate uniform fluorinated SEI on Li‐metal anodes. In Li–sulfur (Li−S) batteries under practical conditions, the fluorinated SEI constructed by AFA undergoes 183 cycles, which is three times the SEI formed by LiNO3. Furthermore, a Li−S pouch cell of 360 Wh kg−1 delivers 25 cycles with AFA. This work demonstrates rational molecular design principles of fluorinated molecules to construct fluorinated SEI for practical Li‐metal batteries. Design principles of fluorinated molecules were proposed to construct a fluorinated solid electrolyte interphase for practical lithium‐metal batteries.